Design and Experimental Testing of Savonius Wind Turbine U Three Blades Type Performance as An Alternative Energy Resource - Arman, Rizky (Kopertis Wilayah X)
Indonesia is famous for its potential natural resource especially energy in the form of mining, water and air. Wind energy is a natural resource that can be obtained for free of charge among the most abundant and available continuously throughout the year. The issue of energy is one of the greatest challenges facing todays society in the world. The utilization of wind energy can be used in sloping areas, mountains, and the waterfront. The principle of conversion of wind energy into electrical energy is as follows: The wind through the blades of the wind turbine spinning pinwheel cause, round lead generator wind turbine spins that into electrical energy. More than 86% of the worlds energy comes from fossil fuels, while the demand for energy worldwide continues to grow rapidly. We all know that the source of non-renewable nature of fossil energy if we only using fossil fuels as an energy source, a current source of energy will be depleted. Then the use of electrical energy derived from fossil also have an effect on the levels of emissions (CO2) in the air so called that the greenhouse effect. The application of wind energy in this study utilized as a small-scale electrical energy plant by utilizing a savonius wind turbine U three blades to generate electricity by using a generator and as a storage current battery. From design calculation results is obtained material on the blade is iron plate with a diameter of 0.6 m and bladeâs high of 0.9 m. The location for this experiment is at the area of gunung panggilun, precisely in building E on 5th floor the Faculty of Industrial Technology, Bung Hatta University.